KETEPATAN WAKTU DALAM PENYAMPAIAN LAPORAN KEUANGAN DI PERUSAHAAN REAL ESTATE DAN PROPERTI - Reny Aziatul Pebriani; RM. Rum Hendarmin; Meilin Veronica (Jurnal Ilmiah Ekonomi Global Masa Kini, 2022)
This study aims to empirically prove the effect on the timely submission of financial statements of real estate and property companies listed on the IDX. The sampling technique in this study used a purposive sampling technique. The data analysis technique used is Descriptive Statistics, Normality Test, Heteroscedasticity Test, Multicollinearity Test, Hypothesis T Test, Hypothesis F Test, and Coefficient of Determination Test. This study uses SPSS version 25. The results of this study conclude that company size affects the timeliness of submitting financial statements, profitability affects the timeliness of submitting financial statements, leverage affects the timeliness of submitting financial statements, liquidity affects the timeliness of submitting financial statements. Company size, profitability, leverage and liquidity simultaneously affect the timeliness of financial report submission.